ENGLISH GUIDE AS A DIDACTIC MATERIAL FOR PROFESSIONAL COMPETENCES ACQUISITION BY STUDENTS OF HOSPITALITY AND TOURSM PROGRAMS (ON THE EXAMPLE OF ‘AWESOME UKRAINE’) - Neliia M. Blynova; Nataliia E. Polishko (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The article discusses the didactic potential of the English-language guide ‘Awesome Ukraine’. In particular, publications dedicated to Lviv, Kharkiv, and Kyiv were analyzed. An editorial analysis was also conducted to determine the specifics of printing, compliance with standards, linguistic features of publications, the level of text content, completeness and appropriateness of illustrative content, i. e. the factors that make the ‘Awesome Ukraine’ series one of the examples of didactic material. Such competencies are neccessary for the bachelor course students in all hospitality programs. In addition, the authors propose types of tasks that will promote better mastering of the material in a foreign language and the acquisition of knowledge of local lore. In the process of learning a foreign language, local lore material can create strong practical skills and abilities to use the language as a means of communication, to provide additional opportunities for further professional growth for the tourism and hospitality professionals. The article proves that the visual and textual components of the researched guides allow to practice techniques of effective professional communication. The material of the publication and the way of its presentation and design can teach tactics and strategies of professional communication, taking into account the essence of national stereotypes of behavior and national and cultural symbols. The research emphasizes that while adopting English-language guides, the specifics of the target audience should be also taken into consideration. However, given the use of these publications as didactic material, we emphasize that the Awesome Ukraine series is suitable for teaching students at the PreIntermediate and Intermediate levels. With the right approach and proper presentation, an Englishlanguage guide can be a powerful source of linguistic and methodological assistance. After all, students not only learn local lore information, but also adopt the way of presenting ideas, the necessary language patterns, learn to apply them in practice by creating their own similar texts. Provided that the future specialist will have to create travel products, the Awesome Ukraine series is a good example to follow. From the point of view of polygraphic design, it should be emphasized that all editions are to acquire a homogeneous design, meaning the each city symbol is to be placed on the cover. The textual content is concise, simple and accessible in English. The materials are illustrated with a thematic photo, which is designed to illustrate the text. The publications are quite competent and created in accordance with publishing standards, embody a well-thought-out concept of presenting textual and illustrative material, crucial for acquiring foreign language competences. The researched guides are a rich source for creating specific didactic exercises necessary for studying the courses, such as «Foreign language for professional purposes» and «Foreign language for special purposes», provided by the bachelor’s program in «Hotel and restaurant business» and «Tourism».